Structure‐specific effects of lipidated oxytocin analogs on intracellular calcium levels, parental behavior, and oxytocin concentrations in the plasma and cerebrospinal fluid in mice. Issue 1 (17th January 2017) - Cherepanov, Stanislav M.; Yokoyama, Shigeru; Mizuno, Akira; Ichinose, Wataru; Lopatina, Olga; Shabalova, Anna A.; Salmina, Alla B.; Yamamoto, Yasuhiko; Okamoto, Hiroshi; Shuto, Satoshi; Higashida, Haruhiro
Abstract: Oxytocin (OT) is a neuroendocrine nonapeptide that plays an important role in social memory and behavior. Nasal administration of OT has been shown to improve trust in healthy humans and social interaction in autistic subjects in some clinical trials. As a central nervous system (CNS) drug, however, OT has two unfavorable characteristics: OT is short‐acting and shows poor permeability across the blood–brain barrier, because it exists in charged form in the plasma and has short half‐life. To overcome these drawbacks, an analog with long‐lasting effects is required. We previously synthesized the analog, lipo‐oxytocin‐1 (LOT‐1), in which two palmitoyl groups are conjugated to the cysteine and tyrosine residues. In this study, we synthesized and evaluated the analogs lipo‐oxytocin‐2 (LOT‐2) and lipo‐oxytocin‐3 (LOT‐3), which feature the conjugation of one palmitoyl group at the cysteine and tyrosine residues, respectively. In human embryonic kidney‐293 cells overexpressing human OT receptors, these three LOTs demonstrated comparably weak effects on the elevation of intracellular free calcium concentrations after OT receptor activation, compared to the effects of OT. The three LOTs and OT exhibited different time‐dependent effects on recovery from impaired pup retrieval behavior in sires of CD38‐knockout mice. Sires treated with LOT‐1 showed the strongest effect, whereas others had no or little effects at 24 h after injection. These results indicated that LOTs have structure‐specific agonistic effects, and suggest that lipidation of OT might have therapeutic benefits for social impairment.